2004
DOI: 10.1101/gr.2505604
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improving Caenorhabditis elegans Phenome Mapping With an ORFeome-Based RNAi Library

Abstract: The recently completed Caenorhabditis elegans genome sequence allows application of high-throughput (HT) approaches for phenotypic analyses using RNA interference (RNAi). As large phenotypic data sets become available, “phenoclustering” strategies can be used to begin understanding the complex molecular networks involved in development and other biological processes. The current HT-RNAi resources represent a great asset for phenotypic profiling but are limited by lack of flexibility. For instance, existing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
745
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 886 publications
(768 citation statements)
references
References 42 publications
21
745
2
Order By: Relevance
“…For RNAi, plasmids were obtained from OpenBiosystems (Rual et al, 2004), sequence verified and seeded on NGM plates as described previously (Lee et al, 2007). For all analysis of cye-1 and additional cell cycle factors, unless noted otherwise, mid-L4 animals were placed on the RNAi plates for 48 hours, dissected and assessed for spatial premature meiotic entry or cell cycle arrest.…”
Section: Rnai Experimentsmentioning
confidence: 99%
“…For RNAi, plasmids were obtained from OpenBiosystems (Rual et al, 2004), sequence verified and seeded on NGM plates as described previously (Lee et al, 2007). For all analysis of cye-1 and additional cell cycle factors, unless noted otherwise, mid-L4 animals were placed on the RNAi plates for 48 hours, dissected and assessed for spatial premature meiotic entry or cell cycle arrest.…”
Section: Rnai Experimentsmentioning
confidence: 99%
“…Complete listing of all KEGG mappings including graphical representation is available at http:// www.nematode.net (Wylie et al, 2004). RNA interference (RNAi) technology was first developed and has been successfully applied to genome-wide gene silencing to reveal gene functions in C. elegans (Fire et al, 1998;Kamath et al, 2003;Rual et al, 2004;Sonnichsen et al, 2005). Caenorhabditis elegans RNAi phenotypes can be further extrapolated in understanding functions of orthologous genes in other nematodes, especially the parasitic nematodes in which complexity of obligate parasitic life cycles and lack of proper laboratory culture system makes high-throughput screening impractical .…”
Section: Functional Categorization and Other Sequence Analysismentioning
confidence: 99%
“…To know whether down-regulation of these proteins has a critical effect on larval development of C. elegans, we observed the RNAi phenotypes of these genes for two generations in CN condition. RNAi phenotypes of sams-1 (Gottschalk et al, 2005), pmt-2 (Sönnichsen et al, 2005), R07H5.8 (Sönnichsen et al, 2005), eef-1A.1 (Simmer et al, 2003), and rla-0 (Rual et al, 2004) were previously reported that they showed larval developmental defects. Unlike those previous reports, we found that RNAi of two out of six CS down-regulated genes, F25H2.10 (rla-0) and R07H5.8, caused severe larval arrest phenotype in the second generation in CN.…”
Section: Discussionmentioning
confidence: 90%